Pengembangan Media Pembelajaran Kartu Truth and Dare untuk Meningkatkan Hasil Belajar Siswa Kelas XI IPA SMAN 1 SAPE - Nuryanti, Nuryanti; Burhanuddin, Burhanuddin; Supriadi, Supriadi (FKIP University of Mataram, 2025)
Research on the development of truth and dare card learning media aims to determine its validity, practicality and effectiveness so that it can improve the learning outcomes of class XI Science students at SMAN 1 Sape. The type of research used is development research (R&D) with the 4D development model (define, design, develop, disseminate) by Thiagarajan (1974). The research sample was 33 students from class XI IPA 6. The research instruments used were expert validation sheets, student and teacher response questionnaire sheets, and pretest-posttest question sheets. The results of the media expert validation test showed an average gain of 93% in the very valid category and the material expert validation test was 94% in the very valid category. The practicality test results were obtained from student and teacher response questionnaires with the same percentage, namely 88%. The results of the effectiveness test were obtained from the students' pretest-posttest results with an N-Gain value of 0.51 which was included in the moderate improvement category. This data shows that the truth and dare card media is suitable for use as a learning medium for thermochemical material for class XI IPA students at SMAN 1 Sape.